TENDENCIES OF DEVELOPMENT AND MODERNIZATION LEGAL EDUCATION IN UKRAINE - Varava, Iryna; Holovko, Svitlana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to determine peculiarities of developing legal education in Ukraine and trends in its modernization in the context of European integration. Methods: the method of historical and legal analysis is used to outline prerequisites for formation and peculiarities of developing legal education in Ukraine; the method of comparative analysis is used to substantiate the ways of modernizing the system of national legal education in the context of harmonization of its standards and technologies with trends in the European educational space; using the method of synthesis, interrelation of goals, functions, content and technologies of modern legal education is determined. Results: the problem of building legal education in Ukraine as a factor in overcoming legal nihilism, meeting the individual’s need for knowledge of law and the legal system, forming legal consciousness and legal culture is actualized; historical and legal features of forming legal education in Ukraine are outlined; it is emphasized that development of a democratic civil society in Ukraine requires a revision of the system of forming legal knowledge among applicants for higher education with an emphasis on conscious compliance with the norms of legal culture; trends in developing legal education in Ukraine are determined and their accordance with European trends is justified. It was concluded that one of the key results of modern legal education is legal competence, legal consciousness and legal culture as a system of legal knowledge, beliefs, skills and personal experience that ensure effective interaction in the legal field. Discussion: effective mechanisms of modernizing legal education in Ukraine and technologies for forming awareness of the importance of rethinking civilizational values in the conditions of military aggression.